Self-efficacy is associated with increased food security in novel food pantry program - Katie S. Martin; Angela G. Colantonio; Katherine Picho; Katie E. Boyle (Elsevier, 2016)
We examined the effect of a novel food pantry intervention (Freshplace) that includes client-choice and motivational interviewing on self-efficacy and food security in food pantry clients. The study was designed as a randomized control trial. Participants were recruited over one year from traditional food pantries in Hartford, CT. Participants were randomized to Freshplace or traditional food pantries (controls) and data collection occurred at baseline with quarterly follow-ups for 18 months. Food security was measured using the USDA 18-item Food Security Module. A newly developed scale was utilized to measure self-efficacy. Scale reliability was measured using a Cronbach alpha test; validity was measured via correlating with a related variable. Analyses included chi-square tests for bivariate analyses and hierarchical linear modeling for longitudinal analyses. A total of 227 adults were randomized to the Freshplace intervention (n=112) or control group (n=115). The overall group was 60% female, 73% Black, mean age=51. The new self-efficacy scale showed good reliability and validity. Self-efficacy was significantly inversely associated with very low food security (p<.05). Being in the Freshplace intervention (p=.01) and higher self-efficacy (p=.04) were independently associated with decreased very low food security. The traditional food pantry model fails to recognize the influence of self-efficacy on a person's food security. A food pantry model with client-choice, motivational interviewing and targeted referral services can increase self-efficacy of clients. Prioritizing the self-efficacy of clients over the efficiency of pantry operations is required to increase food security among disadvantaged populations. Keywords: Food pantry, Freshplace, Self-efficacy, Food security, Client choice